SAT0297 Non-Invasive Assessment of Silent Liver Fibrosis in Patients with Systemic Sclerosis. (10th June 2014) - Vacca, A.; Civolani, A.; Devigus, A.; Fadda, L.; Floris, A.; Porru, G.; Garau, P.; Ibba, V.; Piga, M.; Sorbello, O.; Demelia, L.; Mathieu, A.
Abstract : Background: Although up to 90% of patients systemic sclerosis (SSc) have been estimated to have gastrointestinal involvement, liver disease (without any cause other than SSc itself) has been reported only rarely in this disease. Liver biopsy is considered the gold standard for an accurate assessment of liver fibrosis. However, it is an invasive and expensive tool, so there has been increasing interest in non-invasive assessment evaluation of liver stiffness (LS) by transient elastography (TE) which have been recently demonstrated to be useful for the diagnosis of various grades of fibrosis in the course of chronic liver diseases. Objectives: To evaluate the presence of liver fibrosis in a series of SSc patients, without any functional sign of liver disease and any cause other than SSc itself, and to identify any possible associations with demographic data, disease duration and disease phenotype. Methods: Thirty-nine SSc patients (33 females and 6 males) without liver diseases, mean age 63.4±13.2 years, disease duration 10.5±8, 67 years, and a sex- and age-matched control group, were consecutively studied. LS was evaluated using TE (Fibroscan; Echosens, Paris, France) and measured in kPa. We adopted 5.3 kPa as the cutoff for abnormal LS values. Results: Seventeen (43.5%) SSc patients had abnormal LS values when patients were classified into two groups according to the cutoff (group A <5.3 kPa, group B >5.3 kPa); the median LS value was 4 kPa in group A and 7.1 kPa in group B. There were no significant differences between the two groups in disease duration, demographics, laboratory variables or disease characteristics. Among medications, a significant difference for patients on endothelin receptor antagonist therapy was seen in group B (P=0.02). Conclusions: TE suggested, in a non-invasive fashion, liver fibrosis in 43.5% of our SSc patients, as a result of a primary hepatic involvement. LS measurement could be suggested for checking silent liver fibrosis in SSc, even in absence of abnormal liver function serological tests. However, further studies are required to investigate whether treatment regimens can influence the progression of liver fibrosis, or if they should be modified when abnormal LS values are identified. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3523